Estimating influence of TOE factors on e-government usage: Evidence of Jordanian companies - Thi, Lip Sam; Lim, Hock Eam; Al-Zoubi, Mohammad Issa (Universiti Malaysia Sarawak, 2014)
This paper examines the effect of TOE (Technology, Organizational and External) factors on the usage of e-government among Jordanian public listed companies. Results reveal that in Jordan, companies that are categorized as basic adopters of e-government mainly used e-government for seeking information and contracts (procurement) and TOE factors are generally found to have insignificant effect on the usage. On the other hand, TOE factors are found to have significant effect only on advanced adopters of e-government that mainly used e-government for financial and business integration purposes.